Storytelling for persuasion: Insights from community health workers on how they engage family members to improve adoption of recommended maternal nutrition and breastfeeding behaviours in rural Bangladesh - Grandner, Gargi Wable; Rasmussen, Kathleen M.; Dickin, Katerine L.; Menon, Purnima; Yeh, Tiffany; Hoddinott, John F. (Wiley, 2022)
Community health workers (CHWs) increasingly provide interpersonal counselling to childbearing women and their families to improve adoption of recommended maternal and child nutrition behaviours. Little is known about CHWs' first-hand experiences garnering family support for improving maternal nutrition and breastfeeding practices in low-resource settings. Using focused ethnography, we drew insights from the strategies that CHWs used to persuade influential family members to support recommendations on maternal diet, rest and breastfeeding in a behaviour change communication trial in rural Bangladesh. We interviewed 35 CHWs providing at-home interpersonal counselling to pregnant women and their families in seven ‘Alive & Thrive’ intervention sites. In-depth probing focused on how CHWs addressed lack of family support. Thematic coding based on Fisher's narrative paradigm revealed strategic use of three rhetorical principles by CHWs: ethos (credibility), pathos (emotion) and logos (logic). CHWs reported selectively targeting pregnant women, husbands and mothers-in-law based on their influence on behavioural adoption. Key motivators to support recommended behaviours were improved foetal growth and child intelligence. Improved maternal health was the least motivating outcome, even among mothers. Logically coherent messaging resonated well with husbands, while empathetic counselling was additionally required for mothers. Mothers-in-law were most intransigent, but were persuaded via emotional appeals. Persuasion on maternal rest was most effort-intensive, resulting in contextually appealing but scientifically inaccurate messaging. Our study demonstrates that CHWs can offer important insights on context-relevant, feasible strategies to improve family support and uptake of nutrition recommendations. It also identifies the need for focused CHW training and monitoring to address scientifically flawed counselling narratives.